2016
DOI: 10.1515/georec-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and technology of bricks used for the construction of the XII century ducal castle on the island of Ostrów Tumski, Wrocław (SW Poland)

Abstract: The historic bricks from the ducal castle on Ostrów Tumski (Wrocław), one of the first brickwork structures in the Lower Silesia, which dates back to the XII and XIII century, were studied and characterised by a combination of classical petrographic studies (polarising microscopy), scanning microscopy, thermal analysis and X-ray diffraction. The combined results of these methods suggest that the firing temperature ranges from 950°C, through the most common temperatures of 850–900°C, to the infrequent temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Numerous historical brick buildings have been existed until the 21 st century, which testifies to the strength of such ancient brick materials along centuries of rain storms, snow, thaw-freezing cycles, high temperatures and human-induced deterioration. A large number of studies have been reported about the ancient brick structures and materials to foster their cultural and economic importance as well [11][12][13][14][15][16][17][18][19] . The archaeological clay bricks preservation has given rise to considerable interest of scientists, architects, engineers and archaeologists recently, because the archaeological masonry needs to be restored with the substitution of bricks when they damage.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous historical brick buildings have been existed until the 21 st century, which testifies to the strength of such ancient brick materials along centuries of rain storms, snow, thaw-freezing cycles, high temperatures and human-induced deterioration. A large number of studies have been reported about the ancient brick structures and materials to foster their cultural and economic importance as well [11][12][13][14][15][16][17][18][19] . The archaeological clay bricks preservation has given rise to considerable interest of scientists, architects, engineers and archaeologists recently, because the archaeological masonry needs to be restored with the substitution of bricks when they damage.…”
Section: Introductionmentioning
confidence: 99%
“…The main factor to manufacture these bricks is the clay raw material types used and the firing temperature during their production, because both of these affect the quality and durability of bricks (Mostaghelchi et al 2013;Rasmussen et al 2012;Dunham et al 2001;Dondi et al 1999). A large number of studies have been reported about the ancient brick structures and materials to foster their cultural and economic importance in different parts of the world (Šarić et al 2018;Amadori et al 2017;Shu et al 2017;Bartz & Chorowska 2016;Oguz et al 2014;Fernandes & Lourenço 2007;Cardiano et al 2004;Elert et al 2003;López-Arce et al 2003;Paama et al 2000).…”
Section: Introduction and Objectivementioning
confidence: 99%